2018
DOI: 10.1055/s-0038-1641746
|View full text |Cite
|
Sign up to set email alerts
|

Might Bilirubin Serve as a Natural Antioxidant in Response to Neonatal Encephalopathy?

Abstract: Contrary to our hypothesis, bilirubin concentrations in NE infants are significantly lower than expected during the first 4 days postnatally. We speculate that, under conditions of severe oxidative stress, bilirubin is consumed as an antioxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…As reviewed by Fujiwara et Al. [ 75 ], similar data are present also in neonates [ 72 , 73 , 74 ], where a close association between the plasma bilirubin concentration and the plasma antioxidant capacity has been reported [ 75 ], with icteric neonates showing a favourable plasma antioxidant capacity, that phototherapy worsened [ 173 ]. After more than a century, this supports the speculation that the production of UCB from BV, an unnecessary energy-consuming reaction, is motivated by the benefits of having higher antioxidant defense.…”
Section: The Yellow Players (Yp)supporting
confidence: 61%
“…As reviewed by Fujiwara et Al. [ 75 ], similar data are present also in neonates [ 72 , 73 , 74 ], where a close association between the plasma bilirubin concentration and the plasma antioxidant capacity has been reported [ 75 ], with icteric neonates showing a favourable plasma antioxidant capacity, that phototherapy worsened [ 173 ]. After more than a century, this supports the speculation that the production of UCB from BV, an unnecessary energy-consuming reaction, is motivated by the benefits of having higher antioxidant defense.…”
Section: The Yellow Players (Yp)supporting
confidence: 61%
“…However, accumulating evidence indicates that early physiological increases in serum bilirubin levels in neonates may provide a protective antioxidant defense mechanism to compensate for otherwise deficient antioxidant enzymes, particularly in neonates with increased susceptibility to ischemia/reperfusion injury, such as infants with HIE [7]. In our clinical practice, patients with HIE were less likely to need or did not need phototherapy, and we speculate that bilirubin metabolism may be affected by HIE.…”
Section: Introductionmentioning
confidence: 88%
“…2,3 Bilirubin is a natural antioxidant, and it presumably can protect the body from oxidative stress following birth. 2,3 Some studies have found that serum bilirubin levels following neonatal hypoxic-ischemic injury were lower than those of healthy controls. [3][4][5] These results can be explained by the hypothesis that bilirubin is consumed by scavenging free radicals following the hypoxic event.…”
mentioning
confidence: 99%
“…2,3 Some studies have found that serum bilirubin levels following neonatal hypoxic-ischemic injury were lower than those of healthy controls. [3][4][5] These results can be explained by the hypothesis that bilirubin is consumed by scavenging free radicals following the hypoxic event. [3][4][5] We aimed to investigate the effect of the severity of hypoxic injury on bilirubin levels to clarify this aspect of the physiological role of bilirubin.…”
mentioning
confidence: 99%
See 1 more Smart Citation